The household contact study design for genetic epidemiological studies of infectious diseases - Stein, Catherine; Hall, Noemi B.; Malone, LaShaunda; Mupere, Ezekiel (Frontiers in Genetics, 2013)
Most genetic epidemiological study designs fall into one of two categories: family-based and population-based (case-control). However, recent advances in statistical genetics call for study designs that combine these two approaches. We describe the household contact study design as we have applied it in our several years of study of the epidemiology of tuberculosis. Though we highlight its applicability for genetic epidemiological studies of infectious diseases, there are many facets of this design that are appealing for modern genetic studies, including the simultaneous enrollment of related and unrelated individuals, closely and distantly related individuals, collection of extensive epidemiologic and phenotypic data, and evaluation of effects of shared environment and gene by environment interaction. These study design characteristics are particularly appealing for current sequencing studies.